Insights Into Emissions and Exposures From Use of Industrial-Scale Additive Manufacturing Machines - Stefaniak, A.B.; Johnson, A.R.; du Preez, S.; Hammond, D.R.; Wells, J.R.; Ham, J.E.; LeBouf, R.F.; Martin, S.B.; Duling, M.G.; Bowers, L.N.; Knepp, A.K.; de Beer, D.J.; et al. (Safety and health at work, 2019)
Emerging reports suggest the potential for adverse health effects from exposure to emissions from some additive manufacturing (AM) processes. There is a paucity of real-world data on emissions from AM machines in industrial workplaces and personal exposures among AM operators. Airborne particle and organic chemical emissions and personal exposures were characterized using real-time and time-integrated sampling techniques in four manufacturing facilities using industrial-scale material extrusion and material jetting AM processes. Using a condensation nuclei counter, number-based particle emission rates (ERs) (number/min) from material extrusion AM machines ranged from 4.1 × 1010 (Ultem filament) to 2.2 × 1011 [acrylonitrile butadiene styrene and polycarbonate filaments). For these same machines, total volatile organic compound ERs (μg/min) ranged from 1.9 × 104 (acrylonitrile butadiene styrene and polycarbonate) to 9.4 × 104 (Ultem). For the material jetting machines, the number-based particle ER was higher when the lid was open (2.3 × 1010 number/min) than when the lid was closed (1.5–5.5 × 109 number/min); total volatile organic compound ERs were similar regardless of the lid position. Low levels of acetone, benzene, toluene, and m,p-xylene were common to both AM processes. Carbonyl compounds were detected; however, none were specifically attributed to the AM processes. Personal exposures to metals (aluminum and iron) and eight volatile organic compounds were all below National Institute for Occupational Safety and Health (NIOSH)-recommended exposure levels. Industrial-scale AM machines using thermoplastics and resins released particles and organic vapors into workplace air. More research is needed to understand factors influencing real-world industrial-scale AM process emissions and exposures.